Prevalence and Genetic Characterization of Glucose-6-Phosphate Dehydrogenase Deficiency in Anemic Subjects from Uttar Pradesh, India - Tripathi, Poonam; Agarwal, Sarita; Muthuswamy, Srinivasan (Journal of Pediatric Genetics, 2019)
Glucose-6-phosphate dehydrogenase (G6PD) deficiency is caused by one or more mutations in the G6PD gene on chromosome X. It affects approximately 400 million people worldwide. The purpose of this study was to detect the prevalence of G6PD deficiency and G6PD gene mutations in the hospital-based settings in patients referred for suspected G6PD deficiency. A qualitative fluorescent spot test and dichlorophenol-indolphenol (DCIP) test were performed. G6PD-deficient, positive samples were further processed for mutation analysis by Sanger sequencing. Out of 1,069 cases, 95 (8.8%) were detected as G6PD deficient (by DCIP test) and were sent for molecular analysis. The G6PD Mediterranean mutation (563C > T) is the most common variant among G6PD-deficient individuals followed by the Coimbra (592C→T) and Orissa (131C→G) variants. We concluded that all symptomatic patients (anemic or jaundiced) should be investigated for G6PD deficiency. Our findings will inform our population screening approach and help provide better management for G6PD-deficient patients.
Keywords: G6PD; gene; mutation